Hafnia-doped silicon bond coats manufactured by PVD for SiC/SiC CMCs. (15th January 2020) - Anton, Ronja; Leisner, Vito; Watermeyer, Philipp; Engstler, Michael; Schulz, Uwe
Abstract: SiC/SiC ceramic matrix composites (CMCs) demand an environmental barrier coating (EBC) system when implemented in the hot section of a turbine engine. The connection between EBC and CMC is provided by a bond coat (BC). Numerous reasons make silicon the state-of-the-art BC material but it has some disadvantages regarding long time mechanical behaviour and oxidation resistance. To overcome this, a Si-BC doped with the refractory metal oxide HfO2 is introduced. Two different compositions have been deposited on monolithic SiC by magnetron sputtering. After deposition the coatings are X-ray amorphous, homogenous, columnar structured and virtually free of cracks and pores. Furnace cycle tests up to 1000 cycles were performed at 1523 K. The evolution of microstructure and phases of the coatings were examined employing Scanning Electron Microscopy (SEM), Focused Ion Beam (FIB) serial sectioning, Transmission Electron Microscopy (TEM) and X-ray Diffraction (XRD). During high temperature exposure, the coatings crystallised and the silicon phase started to form a mixed thermally grown oxide (mTGO) layer. The BCs showed evenly distributed hafnia precipitates within the silicon. During testing Ostwald ripening of the precipitates took place. Hafnia slowly reacted with silicon oxide to hafnon (HfSiO4 ). Compared to a pure silicon reference BC, the doped coatings show a better resistance towards crack initiation and spallation up to 1000 h testing time. The results demonstrate that sputtered hafnia-doped Si-BCs are more advantageous for SiC/SiC CMCs with respect to longevity, TGO adherence, and protection of the underlying SiC in comparison to pure Si bond coats. Graphical abstract: Image, graphical abstract